Atmoculture: urban navigation in the age of digital computation - Pavoni, A.; Brighenti, A.M. (Uncommon Senses IV - Sensory Ecologies, Economies, and Aesthetics., 2023)
The notion of ‘atmoculture’ offers a sensory-aware conceptual tool to analyse new forms of urban experience as navigation, in the age of digital computation. Historically, modern urbanisation ushered in a movement-space where the question of psycho-social orientation within an increasingly ‘displaced’ urban space first emerged. We can reconstruct new digital media as a continuation of such spatial imagination. Urban digital navigation, it follows, seems to proceed in parallel with a reorientation of the urban experience towards atmospheric considerations, seeking to maximise safety and pleasure - i.e. comfort - in the urban environment. In this context, atmoculture (referring simultaneously to culture as atmosphere and the culture of atmospheres) appears a spatial-aesthetic, psycho-cultural, and bio-technological milieu that prepares space for convenient navigation. Several consequences follow: first the disburdening effect, that is, the delegation of an increasing number of perceptions and decisions to algorithms themselves, with the consequence of formatting the problem-solving aspect of urban subjectivity into mere solutionism; second, the increasing adaptation to a space invisibly shaped by algorithmically-coded biases; third, the tensional, contradictory outcomes of atmocultural expectations in terms of dependency, atrophy, and stress.